Trend of Halmahera Eddy and Mindanao Eddy - Martono, Martono; Santoso, Heru; Nurlatifah, Amalia; Felix, Mark Jayson (Marine Science Department Diponegoro University, 2024)
Global warming, due to increasing greenhouse gases, has increased the frequency of El Niño Southern Oscillation events and influenced ocean dynamics. This research determined the trends of Mindanao Eddy’s and Halmahera Eddy’s over 28 years (1993–2020). The data used in this research consist of sea surface currents, surface wind, sea surface height, and NIŇO3.4 index. Determination of eddy currents was done using the Automated Eddies Detection method. The results showed that the Asian-Australian monsoon and El Niño Southern Oscillation events influence the characteristics of the Mindanao Eddy and Halmahera Eddy. During the Asian monsoon, the position of the Mindanao Eddy and Halmahera Eddy shifts southward, while during the Australian monsoon, it shifts northward. During El Niño, the position of the Mindanao Eddy turns eastward with a smaller diameter, but the position of the Halmahera Eddy does not shift. Conversely, during La Niña, the position of the Halmahera Eddy turns northwestward with a smaller diameter, while the position of the Mindanao Eddy remains unchanged. The shift of the Mindanao Eddy during the El Niño event is closely related to the weakening of the North Equatorial Current and the strengthening of the North Equatorial Countercurrent. On the other hand, the shift of the Halmahera Eddy during the La Niña event is related to the strengthening of the South Equatorial Current as a source of water masses for the New Guinea Coastal Current. The velocity of the Mindanao Eddy and Halmahera Eddy experienced an increasing trend in 1993-2020.